AKTIVITAS ANTIBAKTERI EKSTRAK KLOROFORM DAUN SIRSAK (Annona muricata L.) TERHADAP PERTUMBUHAN BAKTERI Pseudomonas aeruginosa SECARA IN VITRO - IMAS HAPSARI RAHMANINGTYAS, 061411535001 (2018)
The aim of this research was to study antibacterial activity chloroform extract of soursop leaf (Annona muricata L.) on bacterial growth inhibition of Pseudomonas aeruginosa by diffuse disc method. The result of the inhibition zone was analyzed using Anova (Analysis of Variance) test and followed using Duncan test showed looks outcomes were significantly different (p <0.01). The inhibition number of negative control (K-) was 0,00e ± 0,00 and the positive control (K+) was 31,31a ± 0,57. The result of concentration 1 (P1) was 14,49b ± 4,96; concentration 2 (P2) 8,98c ± 1,29; concentration 3 (P3) 5,84cd ± 1,85; concentration 4 (P4) 5,56cd ± 1,58; concentration 5 (P5) 2,85de ± 0,28; concentration 6 (P6) 2,98de ± 0,53; concentration 7 (P7) 2,82de ± 1,59; concentration 8 (P8) 2,41de ± 1,10; concentration 9 (P9) 2,20de ± 0,34; concentration 10 (P10) 1,1e ± 0,19; and concentration 11 (P11) 0,00e ± 0,00. The increase chloroform extract of soursop leaf concentration showed high inhibition diameter of bacterial growth. It showed that chloroform extract of soursop leaf (Annona muricata L.) have antibacterial activity to inhibit Pseudomonas aeruginosa growth with Minimal Inhibitory Concentration (MIC) 125 ppm.